Does the corticotropin-releasing hormone system play a role in the pathogenesis of lichen planus? - Cemil, Bengu Cevirgen; Yilmazer, Demet; Atas, Hatice; Cengiz, Fatma Pelin; Canpolat, Filiz; Alper, Murat; Gonul, Muzeyyen (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction: Lichen planus (LP) is a chronic inflammatory disease, where the psychogenic factors seem to play an important role in the pathogenesis. Aim: To determine the expression of corticotropin-releasing hormone (CRH) receptor type 1 (CRH-R1) in LP. Material and methods: Thirty-two LP patients and 17 age/gender-matched controls were included in the study. Detailed information about the disease and body surface area (BSA) covered by the lesions was recorded. Immunohistochemically, the expression of CRH-R1 was stained in the lesional skin of patients with LP and in the control group. Results: The comparison of CRH-R1 expression showed a statistically significant difference between LP patients and the controls (p < 0.05). Additionally, we did not observe any correlation between BSA and staining intensity in LP patients. Conclusions: Our study showed an increase in CRH-R1 expression in LP lesions. These results support the participation of the cutaneous CRH/CRH-R1 system in the pathogenesis of LP skin lesions.